Malignant thyroid teratoma: an integrated analysis of case series/case reports. Issue 7 (17th June 2021) - Vuong, Huy Gia; Nguyen, Truong P X; Ngo, Hanh T T; Hassell, Lewis; Kakudo, Kennichi
Abstract : Malignant thyroid teratoma (MTT) is a very rare thyroid malignancy. These neoplasms have been reported only in case reports and small-sized case series so far. In this study, we searched for MTTs in the Surveillance, Epidemiology, and End Result (SEER) program during 1975–2016. Subsequently, we incorporated the SEER data with published MTT cases in the literature to analyze the characteristics and prognostic factors of MTTs. Integrated data were analyzed using chi-square or Fisher's exact test for categorical covariates, and t-test or Mann-Whitney test for continuous variables. We included 28 studies with 36 MTT cases and found additional 8 cases from the SEER program for final analyses. Our results showed that MTT is typically seen in adult females. These neoplasms were associated with an aggressive clinical course with high rates of extrathyroidal extension (80%) and nodal involvement (62%). During follow-up, the development of recurrence and metastases were common (42% and 46%, respectively), and one-third of patients died at the last follow-up. Large tumor size ( P   = 0.022) and the presence of metastases during follow-up ( P   = 0.008) were associated with a higher mortality rate. In conclusion, our study demonstrated the characteristic features of MTT patients and outlined some parameters associated with a negative outcome which could help clinicians better predict the clinical course of these neoplasms.